The use of the open innovation concept to develop a method to improve safety during the mining production process: A case study of the integration of university and industry - Jarosław Brodny; Magdalena Tutak (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Growing competition in the education economy has caused companies to look for new innovative solutions that can increase their competitiveness. These processes practically concern the whole world, and the development of new technologies that are related to the concepts of Industry 4.0 and sustainable economy has accelerated innovation even more. In order to adapt to these trends, companies are taking extensive measures to apply new technologies and implement innovative solutions. The use of an open business model that is based, for example, on the concept of open innovation (OI) could be helpful in this process. By reinforcing their own solutions with external ideas and proposals and by cooperating on joint projects, companies have the chance to maintain beneficial relationships with customers and remain competitive. This also applies to the mining industry, for which the production processes are additionally affected by the natural hazards that are associated with the environment in which these processes are carried out. This article presents a relevant example of using the OI concept to develop and implement an innovative method for reducing the fire hazard that is caused by the spontaneous combustion of coal in underground coal mines. The method was based on the model tests that were conducted by the Silesian University of Technology. Since the mining enterprise in question was looking for an external solution to the problem of the formation and development of endogenous fires, it was open to cooperation. The open exchange of knowledge and ideas resulted in the development of an innovative method that was successfully applied in this coal mine. This paper presents a model for the cooperation between a research unit and an enterprise that included the open exchange of knowledge, which significantly enriched both sides of the project. It also discusses the innovative solution that was developed, which involved the use of model tests to identify potential locations for underground fires and an installation to supply certain substances to these areas in order to limit the occurrence and development of these fires. The results of the research, which confirm the effectiveness of the developed method, are also presented. The application of the IO concept and the cooperation between scientific research and industry made it possible to solve a specific and current problem that has a significant impact on the efficiency of the production processes of mining companies. The implementation of the developed method prevented an endogenic fire, and the mining process proceeded without any major disturbance. The developed solution and the applied model of open cooperation between a research unit and industry could together create the possibility of generating innovative solutions that can be quickly commercialized and implemented. Thus, the concept of OI presents a great opportunity for the development of an innovative knowledge-based economy.
Keywords: 650; coal spontaneous combustion; mining hazards; open innovation; production process; underground fire